Problem-Based Learning To Improve Concept Understanding and Critical Thinking Ability of Science Education Undergraduate Students - Mellyta Uliyandari; Emilia Candrawati; Anna Ayu Herawati; Nurlia Latipah (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
This reserach was conducted to improve conceptual understanding and critical thinking ability of fourth-semester students of the Science education study program, Bengkulu University by applying PBL. The research method used in this study is quasi experimental, which in its implementation uses single class or one group pretest-posttest design. The test question was the instrument used in this study. The findings showed that there was an improvement in students‘ conceptual understanding and critical thinking ability of students‘ since implementing problem-based learning models in environmental chemistry courses. This improvement can be seen from the results of the gain test for each class group on the test of conceptual understanding and critical thinking ability which are in the